Research into Factors Contributing to Discipline Use and Disproportionality in Major Urban Schools - Caven S. Mcloughlin; Amity L. Noltemeyer (Arizona State University, 2010)
Major urban high poverty schools frequently use exclusionary discipline (i.e., out of school suspensions) and apply these consequences disproportionately to African American students. We explored school demographic variables predicting these two outcomes using data from 433 major urban, high poverty schools. Results suggest a different set of predictors for the overall use of suspensions than for disproportionality. Specifically, four variables significantly predicted overall suspension use (office disciplinary referrals; the proportions of African American teachers, economically disadvantaged students, and African American students) whereas only one variable significantly predicted disproportionality (percentage economically disadvantaged students). Implications, limitations and future directions are provided.